Chlorine and fluorine partition coefficients and abundances in sub-arc mantle xenoliths (Kamchatka, Russia): Implications for melt generation and volatile recycling processes in subduction zones - Benard, A.; Koga, K.T.; Shimizu, N.; Kendrick, M. A.; Ionov, Dmitri; Nebel, O.; Arculus, R. J. (Geochimica et Cosmochimica Acta, 2017)
Co-auteur étranger International audience We report chlorine (Cl) and fluorine (F) abundances in minerals, interstitial glasses, and melt inclusions in 12 andesite-hosted, spinel harzburgite xenoliths and crosscutting pyroxenite veins exhumed from the sub-arc lithospheric mantle beneath Avacha volcano in the Kamchatka Arc (NE Russia). The data are used to calculate equilibrium mineral-melt partition coefficients (Dmineral/meltDmineral/melt) for Cl and F relevant to subduction-zone processes and unravel the history of volatile depletion and enrichment mechanisms in an arc setting.Chlorine is ∼100 times more incompatible in pyroxenes (View the MathML sourceDClmineral/melt = 0.005–0.008 [±0.002–0.003]) than F (View the MathML sourceDFmineral/melt = 0.50–0.57 [±0.21–0.24]), which indicates that partial melting of mantle sources leads to strong depletions in Cl relative to F in the residues. The data set in this study suggests a strong control of melt composition on View the MathML sourceDCl,Fpyroxene/melt, in particular H2O contents and Al/(Al + Si), which is in line with recent experiments. Fluorine is compatible in Ca-amphibole in the ‘wet’ sub-arc mantle (View the MathML sourceDFamphibole/melt = 3.5–3.7 [±1.5]) but not Cl (View the MathML sourceDClamphibole/melt = 0.03–0.05 [±0.01–0.03]), indicating that amphibole may fractionate F from Cl in the mantle wedge. The inter-mineral partition coefficients for Cl and F in this study are consistent amongst different harzburgite samples, whether they contain glass or not. In particular, disseminated amphibole hosts much of the Cl and F bulk rock budgets of spinel harzburgites (View the MathML sourceDClamphibole/pyroxene up to 14 and View the MathML sourceDFamphibole/pyroxene up to 40). Chlorine and fluorine are variably enriched (up to 1500 ppm Cl and 750 ppm F) in the parental arc picrite and boninite melts of primitive pyroxenite veins (and related melt inclusions) crosscutting spinel harzburgites.Based on the data in this study, the main inferences on the ...